Ferulic Acid Treatment Maintains the Quality of Fresh-Cut Taro (Colocasia esculenta) During Cold Storage - Wang, Bin; Huang, Yongyan; Zhang, Zhenming; Xiao, Yanhui; Xie, Jing (Frontiers in Nutrition, 2022)
Taro (Colocasia esculenta) is a major root crop or vegetable in the world, and the corm is a good source of many nutrients including starch, vitamins, and minerals. Taro corms are processed into various forms before consumption, which makes them perishable, reduces the shelf life, and increases postharvest losses. The surface browning of fresh-cut taros is one of the major factors that limits storage life and affects consumer acceptance. In this study, the effects of ferulic acid (FA) as an effective agent in the prevention of quality deterioration were investigated. Fresh-cut taros were immersed in distilled water and different concentrations of FA (1, 2, 5, 10, and 20 mM) solutions for 30 min, air-dried at 25°C for 30 min, and then stored at 5°C for 12 days to investigate the effects of FA on browning. Among the FA concentrations tested, 10 mM resulted in significantly higher L* values, lower a* and b*, and browning index values. FA treatment (10 mM) also induced de novo biosynthesis of two volatile compounds, including non-anal and octanoic acid ethyl ester in fresh-cut taros following extended cold storage. The results suggest that FA treatment maintains the quality of fresh-cut taros under cold conditions. FA treatment enhanced PAL activity and gene expression but reduced total phenolic content and the expression of six C4H, 4CL, and CHS genes, suggesting that FA treatment reduced phenolic biosynthesis. FA treatment reduced PPO activity and gene expression and decreased soluble quinone content, suggesting that FA treatment suppressed the phenolic oxidation. FA treatment enhanced the activity and gene expression of CAT and POD, reduced those of LOX, and decreased MDA and H2O2 levels, suggesting that FA treatment activated the antioxidant defense system and thereby reduced oxidative damage. These findings demonstrated that FA treatment could serve as an effective approach to retard the browning of fresh-cut taros and provided a basis for the feasible application of FA in the preservation of fresh-cut foods.